Front Cover: Protonated Ethylene Carbonate: A Highly Resonance‐Stabilized Cation (ChemistryOpen 12/2021). Issue 12 (25th November 2021) - Beck, Stefanie; Jessen, Christoph; Kornath, Andreas J.
Abstract : The Front Cover shows the crystal structure of the salt of protonated ethylene carbonate [C3 H5 O3 ][Sb2 F11 ]. Protonated ethylene carbonate was synthesized by reacting the neutral compound in the superacidic system HF/SbF5 at low temperature. Interestingly, the single‐crystal X‐ray structure analysis revealed a planar CO3 moiety with nearly equal CO bond lengths. Further theoretical investigations of the cation led to the result, that it contains a remarkably delocalized 6π‐electron system. On the cover this resonance stabilization is highlighted by p‐orbitals on the CO3 moiety. More information can be found in the Research Article by Stefanie Beck et al .